Microstructure and magnetic properties of as-cast Ni2MnGa alloys processed by twin roller melt spinning - Pozo Lopez, Gabriela del Valle (2013)
The magnetism and the microstructure of Ni2MnGa alloys, processed by the first time by twin roller melt spinning at tangential wheel speeds of 10 m/s (V10), 15 m/s (V15) and 20 m/s (V20) are investigated. At room temperature, the major phase in the as-cast alloys is the cubic L21 Ni2MnGa ordered austenitic phase, with a lattice parameter only ~0.1% larger than the tabulated value. The order domain size in the austenitic phase decreases from (40±1) nm in samples V10 to (19±1) nm in V20. Mn(S,Se) small precipitates are also found uniformly embedded in the ribbons with mean size of (26±2) nm (V10) and (7±2) nm (V20), exhibiting a definite orientation relation with the austenitic matrix, <100>P // <100>a. The as-cast alloys transform to an intermediate cubic phase I at about 220K-230K depending on the quenching rate and to a martensitic phase at about 130K. The high temperature austenitic phase and the low temperature martensitic phase are ferromagnetic; in both cases the saturation polarization is lower in samples quenched at higher rates. The demagnetization curves measured from saturation in the martensitic state show two marked steps: a first one for positive fields in V15 and V10 (~46 mT) and a larger second one for relatively large inverse fields (~130-250 mT) in all the samples. These steps are likely to arise from a demagnetization mechanism involving a field induced twin boundary motion in the few martensite variants selected by the crystallographic texture and the quenched stresses in the ribbons.